Asymptomatic and Mild SARS-CoV-2 Infections Elicit Lower Immune Activation and Higher Specific Neutralizing Antibodies in Children Than in Adults - Petrara, Maria Raffaella; Bonfante, Francesco; Costenaro, Paola; Cantarutti, Anna; Carmona, Francesco; Ruffoni, Elena; Di Chiara, Costanza; Zanchetta, Marisa; Barzon, Luisa; Donà, Daniele; Da Dalt, Liviana; Bortolami, Alessio; et al. (Frontiers in Immunology, 2021)
Background The immune response plays a pivotal role in dictating the clinical outcome in SARS-CoV-2-infected adults, but it is still poorly investigated in the pediatric population. Methods Of 209 enrolled subjects, 155 patients were confirmed by PCR and/or serology as having COVID-19. Blood samples were obtained at a median of 2.8 [interquartile2.1-3.7] and 6.1 [5.3-7.2] months after baseline (symptom onset and/or first positive virus detection). The immune profiles of activation, senescence, exhaustion and regulatory cells were analysed by flow cytometry. Neutralizing antibodies (nAbs) were detected by a Plaque Reduction Neutralization Test. In available nasopharyngeal swabs at baseline, SARS-CoV-2 levels were quantified by ddPCR. Results Overall, COVID-19 patients had higher levels of immune activation, exhaustion and regulatory cells compared to non-COVID-19 subjects. Within the COVID-19 group, activated and senescent cells were higher in adults than in children, and inversely correlated with the nAbs levels. Conversely, Tregs and Bregs regulatory cells were higher in COVID-19 children compared to adults, and positively correlated with nAbs. Higher immune activation still persisted in adults after 6 months of infection, while children maintained higher levels of regulatory cells. SARS-CoV-2 levels did not differ among age classes. Conclusions Adults displayed higher immune activation and lower production of anti-SARS-CoV-2 nAbs than children. The different immune response was not related to different viral load. The higher expression of regulatory cells in children may contribute to reduce the immune activation, thus leading to a greater specific response against the virus.